EFFECTIVENESS AND SAFETY OF TWO COMBINATION ANTIHYPERTENSIVE THERAPY VARIANTS IN PATIENTS WITH MILD TO MODERATE ARTERIAL HYPERTENSION - S. V. Cheremushkin; Yu. A. Kucheryavyi; T. S. Oganesyan (Российский кардиологический журнал, 2011)
.